Synthesis and Characterization of Photothermal Osmium Carbolong Complexes. Issue 33 (22nd May 2018) - Lin, Qin; Li, Shenyan; Lin, Jianfeng; Chen, Meijin; Lu, Zhengyu; Tang, Chun; Chen, Zhixin; He, Xumin; Chen, Jiangxi; Xia, Haiping
Abstract: Metallacycles with chelating polydentate conjugated‐carbon chain ligands are called carbolong complexes, which are expected to have interesting properties. In this work, the preparation of 12‐carbon carbolong complexes in which all of the coordinated atoms in the equatorial plane are carbon atoms was studied. With the help of the well‐established mechanism, a new approach to prepare coplanar carbolong complexes bearing different organic functional groups was developed by adding different terminal alkynes in sequence. In the presence of HBF4, these coplanar carbolong complexes were converted to η 3 ‐allyl osmapentalene derivatives, which can be produced directly from the reaction of cyclopropaosmapentalene1 with terminal alkynes in the presence of AgBF4 under anhydrous conditions. This study offers a new route for the preparation of functional osmium carbolong complexes with excellent photothermal properties, which can be used to prepare photothermal materials. Abstract : Wet or dry : Photothermal osmium carbolong complexes in which all of the coordinated atoms in the equatorial plane are carbon atoms are a new type of photothermal molecular materials. They can be prepared by a two‐step approach and can be protonated by HBF4 to give η 3 ‐allyl‐functionalized osmapentalene derivatives, which can be produced directly by reaction of the cyclopropaosmapentalene precursor with terminal alkynes in the presence of AgBF4 under anhydrous conditions (see scheme).